2023
DOI: 10.3390/curroncol30050371
|View full text |Cite
|
Sign up to set email alerts
|

Financial Toxicity and Out-of-Pocket Costs for Patients with Head and Neck Cancer

Abstract: Aim: To quantify financial toxicity and out-of-pocket costs for patients with HNC in Australia and explore their relationship with health-related quality of life (HRQoL). Methods: A cross-sectional survey was administered to patients with HNC 1–3 years after radiotherapy at a regional hospital in Australia. The survey included questions on sociodemographics, out-of-pocket expenses, HRQoL, and the Financial Index of Toxicity (FIT) tool. The relationship between high financial toxicity scores (top quartile) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…lost income) and the direct costs of treatment, especially the out-of-pocket expenses for care undertaken in the private health system. 7,8 The funding arrangements for Australia's hybrid public-private system are incredibly complex and patient (and referrers) unfamiliarity with this system can mean high, and often unexpected, out-of-pocket costs. 9 Pricing transparency over the full cycle of care is needed for patients to make informed decisions that take account of their financial circumstances, but is often lacking.…”
Section: Introductionmentioning
confidence: 99%
“…lost income) and the direct costs of treatment, especially the out-of-pocket expenses for care undertaken in the private health system. 7,8 The funding arrangements for Australia's hybrid public-private system are incredibly complex and patient (and referrers) unfamiliarity with this system can mean high, and often unexpected, out-of-pocket costs. 9 Pricing transparency over the full cycle of care is needed for patients to make informed decisions that take account of their financial circumstances, but is often lacking.…”
Section: Introductionmentioning
confidence: 99%
“…With recent advances in cancer treatment and HNC management, the 5-year survival rate of HNC is estimated as 40-50% (3,4). Financial toxicity is a significant issue for some HNC patients, which is associated with a reduced health-related quality of life (5). Additionally, patients with HNC are at significant risk of cardiovascular events; hence, cardiovascular risk mitigation is essential to survivorship care (6).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of out‐of‐pocket costs for cancer care in Australia have been based on these co‐payments, providing valuable information but potentially missing other health care‐related out‐of‐pocket costs, such as unsubsidised care and treatment‐related travel and accommodation 5 . Other studies have included a broader range of cost types, but were limited to selected cancer types or a single rural area 6‐8 . Nevertheless, some studies have reported very high out‐of‐pocket health care costs 9,10 that could lead to inequities in health care, particularly if timely access to all treatment options is available only to people with adequate financial resources 11 .…”
mentioning
confidence: 99%